تكريم الإنسان في الميراث الشرعي الإسلامي دراسة مقارنة - الاحمد, سهيل (University of Eloued جامعة الوادي, 2020)
ملخص: تناولت هذه الدراسة تكريم الإنسان في الميراث الشرعي دراسة مقارنة، هادفة إلى التعرف على طبيعة تكريم الإنسان ومظاهر ذلك ونطاق تطبيقه في الميراث الإسلامي. وقد تم الوقوف على ماهية الميراث، وأهميته ومصادره في المفهوم الشرعي، وكذلك بيان كيف يكون التوريث عند بعض الشرائع والقوانين قديمًا وحديثًا، حيث ظهر أن التشريع الإرثي قد عالج علاقة الإنسان بالاستخلاف في الأرض وعمارتها وتنميتها، وهو قد بين كذلك حدود كسب المال من خلال هذا الميراث، ووقف البحث على حقيقة التكفل ببيان التوزيعات الشرعية للأنصبة الإرثية وبأن ذلك قد جاء من خلال نصوص القرآن الكريم المفصلة الواضحة، وتوصل إلى أن هذه التقسيمات لم تستثن أفراد المجتمع الإنساني من الميراث فالمرأة ترث كما يرث الرجل، ويرث الصغير والمجنون كما يرث الكبير والعاقل وفق تفصيلات وردت في هذا البحث. Abstract This study examines ‘Honoring Human in the Legal Inheritance: A comparative study’. It aims at identifying the nature of human honor, its manifestations, and the scope of its application in the Islamic inheritance. The nature of the inheritance, its importance and its resources have been examined in the legal concept, as well as an explanation of how inheritance in some ancient and modern laws is addressed. It has been found that that inheritance legislation has dealt with the relationship of man to succession in our planet, its maintenance and development. The legislation has also indicated the limits of earning money through this inheritance. The researcher has also explored the fact of legal distributions of inheritance shares, and clarified that these distributions come through the clear and detailed discourse of the Noble Qur’an. Finally, it has been concluded that these divisions did not exclude any member of the human society from the inheritance: Woman can inherit like her counterpart the male, children and young men as well as the elder and sane can also inherit according to some details referred to in this paper
مقال
Keywords: الميراث- التشريع الإسلامي- تكريم الإنسان- الميراث وعمارة الأرض- الإرث. ; Inheritance, Islamic Legislation, Honoring Human, Inheritance for Urbanism, Legacy